DEVELOPMENT SYSTEM MODELS AS A BASIS ORGANIZATIONAL-TECHNOLOGICAL SYSTEMS CONTROL THE LIFE CYCLE OF AN AERONAUTICS - Тамаргазін, О.; Крамаренко, Т. (Science-based technologies, 2011)
In  the  article  the  gear  of  interacting  of  organizational-technological  systems  in  structure  of  life  cycle  of  a  modern aeronautics is observed. It was thus considered, that the structure vital to an aeronautics cycle charac-terizes it as an element of hierarchical system in structure of all air-transport complex. The analysis of this prob-lem  has  allowed  to  open gears  direction  of  operation achievement  and  to determine the primary  goals  of  inte-gration of organizational-technological systems on all stages of life cycle of an aeronautics.